Uji Daya Antibakteri Ekstrak Etanol Kayu Siwak (Salvadora Persica) Terhadap Pertumbuhan Bakteri Porphyromonas Gingivalis Penyebab Gingivitis In Vitro - Karima, Aftina Mutiara, drg. Mahmud Kholifa, MDSc, drg. SE Yuletnawati, MDSc (2014)
Gingivitis is one of frequent periodontal disease. one of bacteria that was known can caused gingivitis is Porphyromonas gingivalis. to prevent gingivitis there was an alternative treatment by using siwak (Salvadora persica). siwak is one of herbs that was believed can resist Porphyromonas gingivalis growth. siwak antibacterial reaistance came from its active substances such as flavomoid, tannin and saponin. this study was conducted to examine antibacterial resistance of siwak (Salvadora persica) ethanol extract against Porphyromonas gingivalis growth and to find out exact proportion of siwak ethanol extract that give the most inhibition effect against its growth in vitro. This laboratory experiment divided the subject into 5 treatment groups, while each groups were given different concentration of siwak ethanol extract 20%, 40% and 80% sterile aquades and 0.2% of chlorhexidine, and was repeated for 5 times. the subjects were put on petri dish, treated with diffusion disk Kirby-bauer method on 37C incubation wihtin 48 hours. Clear zone appeared arround the disk was measured in millimeter degree using vernier calipers. the data retrieved were then calculated using one way Anova test, followed by LSD Post-hoc test in confidence degree 95%. The result showed that there was antibacterial power of siwak (Salvadora persica) ethanol extract against gingivitis bacteria Porphyromknas gingivalis growth on 20%, 40% and 80% concentration and 0.2% chlorhexidine. there was no sign of inhibition zone existence from sterilized aquades. it can be concluded that siwak (Salvadora persica) ethanol extract potentially inhibit Porphyromonas gingivalis growth in vitro.